1985
DOI: 10.1042/bj2320863
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence quenching of human orosomucoid. Accessibility to drugs and small quenching agents

Abstract: The fluorescence behaviour of human orosomucoid was investigated. The intrinsic fluorescence was more accessible to acrylamide than to the slightly larger succinimide, indicating limited accessibility to part of the tryptophan population. Although I- showed almost no quenching, that of Cs+ was enhanced, and suggested a region of negative charge proximal to an emitting tryptophan residue. Removal of more than 90% of sialic acid from the glycan chains led to no change in the Cs+, I-, succinimide or acrylamide qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The IC 50 was determined by use of an Excel software-based line graphic template after plotting the concentration value of each sample against percent inhibition of motility of the parasite on the x and y axes, respectively (41). The motility data were considered for evaluating IC 50 s. An in vitro cytotoxicity assay with all the test samples was carried out for assessment of the 50% cytotoxicity concentration (CC 50 ), as described earlier (42). The selectivity index (SI) was calculated as CC 50 /IC 50 to determine the therapeutic window for safety for the use of the compounds in animals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IC 50 was determined by use of an Excel software-based line graphic template after plotting the concentration value of each sample against percent inhibition of motility of the parasite on the x and y axes, respectively (41). The motility data were considered for evaluating IC 50 s. An in vitro cytotoxicity assay with all the test samples was carried out for assessment of the 50% cytotoxicity concentration (CC 50 ), as described earlier (42). The selectivity index (SI) was calculated as CC 50 /IC 50 to determine the therapeutic window for safety for the use of the compounds in animals.…”
Section: Methodsmentioning
confidence: 99%
“…The motility data were considered for evaluating IC 50 s. An in vitro cytotoxicity assay with all the test samples was carried out for assessment of the 50% cytotoxicity concentration (CC 50 ), as described earlier (42). The selectivity index (SI) was calculated as CC 50 /IC 50 to determine the therapeutic window for safety for the use of the compounds in animals. The compounds with SIs of Ն10 were considered safe and further used for in vivo evaluation in animal models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 of 3 Trp residues of hAGP are relatively shielded from the bulk solvent, whereas the third Trp residue is located on the periphery of the domain. It has been deduced that Trp-25 is located deep in the binding pocket, and that Trp-122 is located in the central hydrophobic pocket of the protein (65). This suggests that Trp-160 is the Trp residue that is exposed to the bulk solvent.…”
mentioning
confidence: 99%
“…Researchers have proposed that the protein has the potential for stereoselective hydrogen bonding, 11,16,[19][20][21] as well as ion exchange. 10,12,22 Research has also shown that chiral retention of many classes of drugs are dominated by a hydrophobic interaction with the core of the AGP.…”
mentioning
confidence: 99%